Impact of Consortia on Usage Pattern of Information Resources: a Study at Raman Research Institute - Manjunath, M.; Kaddipujar, Manjunath; Meera, B. M. (Journal of Information and Knowledge, 2013)
The concept of consortia has been in vogue in library profession for quite some time. It has taken firm root in librarianship due to the evolution and revolution of “Digital Information”. Shrinking budget and the rate of growth of publications in digital format has encouraged librarians to view consortia as their friend. CSIRDST consortium re-designated as National Knowledge Resource Consortia (NKRC) had its beginning in 2009. Since then, Raman Research Institute is an active partner and a stake holder of this consortium. The benefits of consortia can best be assessed either by usage statistics or by analyzing the cited references of the research papers published by the scientists of an institute. In this study, the later method has been adopted to study the impact of consortium at Raman Research Institute. Cited references of the papers published prior to consortia are compared against the papers published three years after joining the consortia. It is envisaged that this study will throw light on the usage pattern of information resources with respect to subscribed content and shared content through consortia.